A Study of the Relationship Between Mental Health and Online Platforms for Education - Nastaran Kazemi Rad; Atefeh Mohammad Jafari; Zahra Mirsepassi; Pedram Sarikhani (BJPsych Open, 2025)
Aims: 1. Providing practical solutions for richer and broader use of online platforms for education among students. 2. Finding factors related to online education that are involved in causing mental disorders in students and preventing and correcting them.